Fusion protein of retinol‐binding protein and albumin domain III reduces liver fibrosis. Issue 6 (11th April 2015) - Lee, Hongsik; Jeong, Hyeyeun; Park, Sangeun; Yoo, Wonbaek; Choi, Soyoung; Choi, Kyungmin; Lee, Min‐Goo; Lee, Mihwa; Cha, DaeRyong; Kim, Young‐Sik; Han, Jeeyoung; Kim, Wonkon; et al.
Abstract Activated hepatic stellate cells (HSCs) play a key role in liver fibrosis, and inactivating HSCs has been considered a promising therapeutic approach. We previously showed that albumin and its derivative designed for stellate cell‐targeting, retinol‐binding protein–albumin domain III fusion protein (referred to as R‐III), inactivate cultured HSCs. Here, we investigated the mechanism of action of albumin/R‐III in HSCs and examined the anti‐fibrotic potential of R‐III in vivo. R‐III treatment and albumin expression downregulated retinoic acid (RA) signaling which was involved in HSC activation. RA receptor agonist and retinaldehyde dehydrogenase overexpression abolished the anti‐fibrotic effect of R‐III and albumin, respectively. R‐III uptake into cultured HSCs was significantly decreased by siRNA‐STRA6, and injected R‐III was localized predominantly in HSCs in liver. Importantly, R‐III administration reduced CCl4‐ and bile duct ligation‐induced liver fibrosis. R‐III also exhibited a preventive effect against CCl4‐inducd liver fibrosis. These findings suggest that the anti‐fibrotic effect of albumin/R‐III is, at least in part, mediated by downregulation of RA signaling and that R‐III is a good candidate as a novel anti‐fibrotic drug.